2018
DOI: 10.1590/1983-21252018v31n124rc
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Phenolic Compounds and Antioxidant Activity in Cowpeas of BRS Xiquexique Cultivar

Abstract: Cowpea (Vigna unguiculata [L.] Walp.) is one of the most important legumes produced in tropical and subtropical regions throughout the world, especially in the developing countries in Africa, Latin America, and Asia. It is the main source of protein, calories, dietary fiber, minerals, and vitamins for a large segment of the world population. Cowpea is also a potential functional food with a range of bioactive compounds, including phenolic compounds. This legume is grown mainly in the North and Northeast region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
1
12
0
4
Order By: Relevance
“…According to Moreira-Araújo et al (2018) among the phenolic compounds identified in cowpea, stood out the catechin (2.07 to 6.48 mg/100g), epicatechin (0.48 to 8.67 mg/100g), gallic acid (45.4 to 93.4 mg/100g), ferulic acid (11.1 to 32.07 mg/100g) and chlorogenic acid (0.59 to 3.08 mg/100g).…”
Section: Resultsmentioning
confidence: 99%
“…According to Moreira-Araújo et al (2018) among the phenolic compounds identified in cowpea, stood out the catechin (2.07 to 6.48 mg/100g), epicatechin (0.48 to 8.67 mg/100g), gallic acid (45.4 to 93.4 mg/100g), ferulic acid (11.1 to 32.07 mg/100g) and chlorogenic acid (0.59 to 3.08 mg/100g).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, in the specific case of immature seeds from this genotype, it was observed an increase of all parameters under water stress against the control group suggesting that this genotype is more tolerant to drought stress and can be a good choice in the climate changes context and in regions with water scarcity. To confirm this hypothesis, it would be important in a near future to fingerprint, in different water‐deficit stresses, the major individual phenolic compounds previously identified in cowpea, namely catechin, epicatechin, gallic acid, ferulic acid and chlorogenic acid (Moreira‐Araújo et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Moreira‐Araújo et al. (2018) classified cowpea as a moderate crop in relation to phenolic content. Probably, these differences can be explained by the interference of genetic and environmental factors, as well as factors inherent to extraction methodology (as the solvent used).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the direct infusion of the corresponding standard solutions for GLSs and PHs was performed. GLSs were quantified using sinigrin (Sigma) as standard compound, whereas glycosylated and acylated flavonoids were quantified as quercetin‐3‐rutinoside, and hydroxycinnamic acids as sinapic acid, as recommended by Moreira‐Araújo et al . Each standard solution prepared at a concentration of 10 mg mL −1 of 70% (v/v) methanol was infused separately into the mass spectrometer at a flow rate of 5 mL min −1 , to optimize parameters such as declustering potential, focusing potential and entrance potential.…”
Section: Methodsmentioning
confidence: 99%